Eﬀectiveness of combined therapy in physical therapy for the management of musculoskeletal pain: a systematic review and meta-analysis - de la Barra Ortiz, Hernán Andrés; Alfaro Leiva, Cristóbal; Alfaro Lillo, Camilo; Carvajal Álvarez, Diego; Cuéllar Pizarro, Bastián (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Therapeutic ultrasound and electrotherapy are commonly used in physical therapy for musculoskeletal pain (MSP) management. Combined therapy (CT) is a resource that merges both techniques, enhancing the analgesic eﬀects of both treatments, although studies are limited. Objective: To determine the eﬀectiveness of CT in physical therapy for the manage-ment of MSP.Methods. The PubMed, Web of Science, Scopus, Cinahl, Science Direct, and PEDro databases were searched for randomised clinical trials (RCTs) (updated June 5, 2024). RCTs comparing CT with other physical therapy treatments for MSP were included. Thirteen studies met the eligibility criteria, including those of the qualitative synthesis and meta-analysis types. The Cochrane Rob2 tool was used to assess the articles’ quality.Results. RCTs were assessed as having a low risk of bias for all RoB2 domains. Although the qualitative synthesis reports a reduction in pain, an increase in ROM, and less disability in favour of CT, the quantitative analysis only shows large, statisti-cally signiﬁcant eﬀect sizes (Cohen’s d) (p < 0.05) for the standardised mean diﬀerences (SMD) in pain (SMD = 0.9; CI = 0.8, 1.1) and ROM (SMD = –0.93; CI = –1.1, –0.8). These analgesic and ROM beneﬁts improve when CT is applied with interferential cur-rents (Pain: SMD = –1.54; IC = –1.8, –1.3) (ROM: SMD = 2.28; CI = 1.8, 2.7). Although the analgesic evidence was qualiﬁed as important, the heterogeneity obtained in the studies (I2 > 75%) moderates its degree of recommendation.Conclusions. This SR shows that CT has better analgesic eﬀects than TENS, interferential currents, or therapeutic ultrasound alone, which supports the idea of a combined analgesic eﬀect. The researchers propose dosage recommendations for clinical practice and future research.
Keywords: electrical stimulation therapy; musculoskeletal diseases; therapeutic ultrasound; transcuta-neous electrical nerve stimulation; musculoskeletal pain; systematic review